Utilization of the smoking cessation clinic at Public Health Centre 1 North Denpasar: A qualitative study - Sri Idayani; Putu Ayu Indrayathi; Dyah Pradnyaparamita Duarsa; Dinar Lubis (Universitas Udayana, 2018)
Background and purpose: The incidence of morbidity and mortality due to tobacco use is very high. There are several strategies to help smokers quit, one of which is counseling to stop smoking in a clinic setting. The purpose of this study was to explore in depth the utilization of smoking cessation clinics at a Public Health Centre (PHC). Methods: A qualitative study through in-depth interviews was conducted with 14 informants who had been provided with a counseling at a smoking cessation clinic, consisting of five informants who had quit smoking and nine informants who were still smoking. Triangulation of data was carried out by conducting in-depth interviews with the head of PHC and one counselor on duty at the smoking cessation clinic. The information collected includes the utilization of the clinic, strategy of PHC in recruiting patients, knowledge about smoking cessation and the benefits of attending counseling. Data collection was carried out at the home of each informant during March-April 2018. The results of the interviews were analyzed thematically after a verbatim transcription being conducted. The data presented in a narrative to provide an in-depth description of the utilization of smoking cessation clinics in a PHC. Results: The results of interviews with PHC staff showed that in order to increase the utilization of the smoking cessation clinic, the services are integrated into the general polyclinic. Interviews with informants who have not stopped smoking indicate that to improve the utilization of the clinic, promotion and service variations are needed and not only focus on counseling. Interviews with informants who have stopped smoking show that counseling at the clinic can increase their willingness to stop smoking. Conclusion: To improve the utilization of smoking cessation clinics, in addition to integrating services into the general polyclinic, promotion and variations in services are also required.